Amino Acid‐triggered Water‐soluble NBD Derivatives for Differential Organelle Staining and the Role of the Chemical Moiety for their Specific Localization. Issue 20 (22nd September 2022) - Mandal, Subhasis; Singh, Arpana; Paul, Subhojit; Ghosh, Arnab; Sen, Prosenjit
Abstract: Apart from being the unit of proteins, amino acids have diverse roles. Here we have shown that amino acids guide the differential transportation of a dye molecule to the cellular organelles depending upon the property of their intrinsic functionality. We have conjugated the nitrobenzofurazan (NBD) moiety with two amino acids (lysine and histidine derivatives) with a linker. Both derivates are water‐soluble and biocompatible in nature. Surprisingly, we found that lysine‐conjugated NBD (NBD‐Lys) stains lipid droplets whereas histidine‐conjugated NBD (NBD‐His) stains lysosomes. We also measured the spectral properties of these two NBD conjugates. The results depict that both conjugates are extremely stable both in air and under inert atmosphere, and the fluorescence of the derivatives remains almost unaltered at different pH. Further by altering the functionality of the side chain, we established the contribution of each functional group towards this differential organelle targeting. Abstract : Synthesized NBD‐Lys localized at lipid droplet whereas NBD‐His stains the lysosome. The imidazole moiety in histidine is playing the key role for specific staining of lysosome.